Gender-Based Violence as a Barrier to Women's Economic and Social Decision-Making: A Legal Analysis - Kumar, Sanjeev; Singh, Sanjeet (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Sexual violence against women and girls is arguably the most serious challenge to women's economic and social empowerment in India. The low status of women in India seems unaffected in the face of the menace of patriarchal norms, inadequate enforcement of law, and societal stigma opposed to their rights and opportunities, despite the establishment of a broad legal framework enshrined in several statutes including the Constitution, Protection of Women from Domestic Violence Act (2005), Sexual Harassment at Workplace Act (2013), and the recently adopted Bharatiya Nyaya Sanhita (2023). This continues to affect women, preventing them from participating in the workforce, accessing education and skill development opportunities, and gaining political representation, among others. If therapist involvement is absolutely necessary, it is primarily because of the victim's immeasurable economic reliance on her abuser, complete ignorance of her legal rights or protections, and total absence of adequate institutional support. The intersectionality of caste, class, and geography also influences women's experiences of violence, and women from marginalized groups still find justice out of reach. In this study, GBV and its effect on women's autonomy and decision-making have been well-documented from legal, economic, and social perspectives. It describes obstacles to the implementation of laws and policies, including lengthy trials, underreporting, corruption, and inadequate rehabilitation services. It also recommends policies to strengthen law enforcement, improve survivor support systems, increase workplace protections, and promote gender-sensitive legal reforms. It is also important to realize that a rights-based approach is essential in order to promote women's ability to plan for their lives, make their own decisions, develop sustainable livelihoods, and fully participate not only in decision-making but also in the economic growth of the nation. Yet, it has been observed that even in the absence of the aforementioned measures, GBV will continue to impede gender equality and sustainable growth of the country.